P-175THROMBOCYTOSIS INDUCED BY SURGERY IN NON-SMALL-CELL LUNG CANCER PATIENTS. (June 2014) - Kouritas, Vasileios; Bellenis, I.; Psevdi, A.; Zisis, C.
Abstract : Objectives: Thrombocytosis is considered a poor prognostic factor of survival in non-small-cell lung cancer (NSCLC) patients. Whether surgery has an effect upon thrombocytosis has not been adequately investigated. The aim of the study is to detect if surgery affects the appearance of thrombocytosis in surgically-treated NSCLC patients. Methods: The records of 270 patients operated for NSCLC during 2 consecutive years (2009-2010) were retrospectively analyzed. Data reviewed included the demographic data, the stage and type of NSCLC, the type of surgery performed, the invasion of the visceral pleura and the invasion of the bronchial margins. The number of platelets was determined before surgery, the next day, every 2 days postoperatively until the first postoperative month, and during the follow-up period. Thrombocytosis was considered when a value of platelets ≥400x10 3 /mm 3 was measured. Results: Two hundred were men. The mean age was 60.8 ± 14.5 years. Preoperative thrombocytosis was observed in 21 patients (7.8%), while postoperative thrombocytosis was found in 119 (44.1%, P = 0.030) . The median time after surgery for thrombocytosis was 0.3 months. Postoperative thrombocytosis was observed more frequently in pneumonectomies (56.4%) and lobectomies (49.3%) when compared to atypical tumour excisions (32.2%, P = 0.012). No association was found between postoperative thrombocytosis and oncological parameters. Thrombocytosis was higher after surgery (376, 192 ± 130, 877 vs 245, 375 ± 112, 938, P = 0.0001) even in preoperative thrombocytosis cases (635, 000 ± 186, 996 vs 493, 187 ± 113, 150, P = 0.009). Similar observations were made for benign cases. Multivariate analysis revealed that the type of surgery was independently associated with postoperative thrombocytosis, whereas the stage of the disease is related to the preoperative thrombocytosis. Conclusions: Postoperative thrombocytosis is not related to oncological parameters but to the extent of the resection. Surgical stress seems to be the cause of postoperative thrombocytosis. On the contrary, preoperative thrombocytosis is related to the stage of the disease, and clinicians might include it in the study of oncological components. Disclosure: No significant relationships.